2020
DOI: 10.3389/fonc.2020.00005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Symbiosis in Chemoresistance: Refocusing the Role of Aerobic Glycolysis

Abstract: Cellular metabolic reprogramming is now recognized as a hallmark of tumors. Altered tumor metabolism determines the malignant biological behaviors and phenotypes of cancer. More recently, studies have begun to reveal that cancer cells generally exhibit increased glycolysis or oxidative phosphorylation (OXPHOS) for Adenosine Triphosphate(ATP)generation, which is frequently associated with drug resistance. The metabolism of drug-resistant cells is regulated by the PI3K/AKT/mTOR pathway which ultimately confer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 72 publications
2
84
0
Order By: Relevance
“…In the current study, we observed the anti-CRC functions of 5-FU in a dose-dependent manner as expected, whereas the overexpression of STK35 in CRC cells partially reversed these effects, such as the promotion of apoptosis, tumor growth inhibition, and survival improvement in an in vivo mouse model. Additionally, previous studies have illustrated that reprogrammed glycolysis, as a recognized hallmark for malignancy which generates plentiful intermediate functional products, also contributes to cancer resistance toward therapeutic drugs (Qian et al, 2017;Ma and Zong, 2020), which is in accordance with our findings in the present study. All these results suggest that STK35 is capable of influencing CRC chemoresistance toward 5-FU, partially attributed to its role in the induction of the glycolytic process in cancerous cells, while, to a further extent, targeting STK35 downregulation in CRC patients might improve the efficacy of chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we observed the anti-CRC functions of 5-FU in a dose-dependent manner as expected, whereas the overexpression of STK35 in CRC cells partially reversed these effects, such as the promotion of apoptosis, tumor growth inhibition, and survival improvement in an in vivo mouse model. Additionally, previous studies have illustrated that reprogrammed glycolysis, as a recognized hallmark for malignancy which generates plentiful intermediate functional products, also contributes to cancer resistance toward therapeutic drugs (Qian et al, 2017;Ma and Zong, 2020), which is in accordance with our findings in the present study. All these results suggest that STK35 is capable of influencing CRC chemoresistance toward 5-FU, partially attributed to its role in the induction of the glycolytic process in cancerous cells, while, to a further extent, targeting STK35 downregulation in CRC patients might improve the efficacy of chemotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this, increased activity of key mediators of glycogen metabolism (glucose, AKT, GSK, and AMPK) is strongly associated with chemoresistance (84)(85)(86). Mechanistically, it appears that glycogen-derived metabolites contribute to chemotherapy resistance via a variety of mechanisms, including via ATP-based drug efflux and ROS protection, however more work is required to understand these processes (87).…”
Section: Glycogen and Chemoresistancementioning
confidence: 75%
“…Cancer cells rely on higher rates of aerobic glycolysis as their primary source of energy, even in the presence of oxygen (known as Warburg effect) [ 10 ], thus promoting cancer cell proliferation, cancer progression, and resistance to apoptotic cell death [ 11 ]. This aberrant tumor glucose metabolism and the increased rates of glycolysis in tumors are correlated to intrinsic/acquired resistance to routinely used anticancer drugs [ 11 , 12 , 13 ]. In this review, we focus on various ways to target the aberrant metabolism that should serve as a promising strategy for chemosensitizing tumors and overcoming resistance in BC, thus effectively treating BC with minimal side-effects and blocking invasion, metastasis, and incidence of recurrence in affected individuals.…”
Section: Introductionmentioning
confidence: 99%